RECONSTRUCTION PROTECTION OF LAW OF VICTIMS OF VICTIMS BASED ON JUSTICE VALUES - ervin hengki (UNISSULA, 2017)
The crime of rape is the most difficult case in the settlement, either at the stage of investigation, prosecution, or at the stage of the adjudication of the verdict. Legal protection of victims of criminal rape in positive law in Indonesia is currently not based on the value of justice, because there are still weaknesses, namely the weakness of the law, the weakness of the approach / way of thinking of law enforcers, as well as the weaknesses during the criminal justice process.